Correlation between Cadmium and Lead Levels in Maternal Blood Samples with Preterm Labor - Ghalib, Maryam Najah Ali; Yassen, Najah Shaker; Ali, Miami Abdulhasan; Ahmed, Haider Abdulhussein (Journal of Science in Medicine and Life, 2025)
Background: Globally, an estimated one million children under the age of five die every year as a direct result of preterm birth and its associated consequences. Preterm birth has a complicated and multi-factored etiology. Prenatal exposure to heavy metals is widely believed to have a significant role in the genesis of preterm birth. Aim of study: To estimate the association between maternal blood lead and cadmium on one hand, and preterm labor on the other hand. Study design and setting: This is a case-control study that included 100 patients (50 cases and 50 controls) and was conducted in Baghdad Teaching Hospital/ Medical city, Baghdad in the period from the 1st of January 2022 to the 30th of November 2022. Methodology: Preterm birth was defined as birth at gestational age less than 37 weeks and term pregnancy³37 completed weeks. Testing for blood lead and cadmium levels was conducted in the Iraqi Poisoning Consultation Center of Baghdad Medical City. Results: The mean blood lead of the studied sample was 20.8 μg/dl ± 5.4. The mean cadmium lead was 0.26 μg/dl ± 0.08, which was significantly higher than the level considered acceptable by the World Health Organization. For blood lead, using cut-off value of 0.3 μg/dl for blood lead as accepted by the Iraqi center of toxicity), the women with preterm labor had significantly higher levels of blood lead than women with term labor. A cut-off value of 0.3 μg/dl had a sensitivity of 48%, specificity of 100%, postivie predictive value of 100%, negative predictive value of 65.7%, and accuracy of 74%. As for blood Cd, using cut-off value of 0.3 μg/dl for blood cadmium as accepted by the Iraqi center of toxicity), the women with preterm labor had significantly higher levels of blood Cadmium than women with term labor. a sensitivity of 68%, specificity of 100%, postivie predictive value of 100%, negative predictive value of 75.7%, and accuracy of 84%. Conclusion: Maternal blood lead and cadmium levels were extremely higher than the level considered acceptable by the World Health Organization and considerably higher than other studies. Moreover, the present study found that both studied heavy metals may contribute as risk factors of preterm labor.